RESEARCH ON THE QUAIL EGGS ALBUMEN CONTENT IN SOME HEAVY METALS - I. VIZITIU (International Journal of Medical Dentistry, 2015)
Out of a sample batch of 20 Japanese quails, Pharaoh race, with an age of 100 days and weighing 245 g, approximately 200 eggs were collected at the peak phase of the laying period. The eggs were measured, weighed and broken, separating the albumen from the other components. The data obtained served to calculate the physical and morphological indices. Primary chemical composition, caloricity, heavy metals content were first determined, the following data being obtained: quail eggs albumen has an average weight of 7.1025±0.061g, an average volume of 7.158±0.09cm3, an average density of 1.0168±0.0139 g/cm3 and an index (of freshness) of 0.0797±0.0015. The albumen contains: 86.76% water, 13.24% dry matter, 0.835% mineral matter, 11.37% protein, 1.03% non-nitrogenous extractive substances and a caloricity of 289.498 kJ for 100 g product. The average content of heavy metals in albumen was: 1.33*10-3 ppm, for cadmium; 8.83*10-2 ppm, for zinc; 1.005 ppm, for cooper and 0.0 ppm, respectively, for lead.